Polymer light emitting devices with Langmuir Blodgett (LB) films of a polyfluorene derivative - Olivati, Clarissa A. [UNESP]; Ferreira, Marystela [UNESP]; Machado, Angelita M.; Akcelrud, Leni; Giacometti, José A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
Polyfluorenes are promising materials for the emitting layer of polymer light emitting devices (PLEDs) with blue emission. In this work, we report on PLEDs fabricated with Langmuir-Blodgett (LB) films of a polyfluorene derivative, namely poly(9,9-di-hexylfluorenediyl vinylene-alt-1,4-phenylenevinylene) (PDHF-PV). Y-type LB films were transferred onto ITO substrates at a surface pressure of 35 mN m-1 and with dipping speed of 3 mm min -1. A thin aluminum layer was evaporated on top of the LB film, thus yielding a sandwich structure (ITO/PDHF-PV(LB)/Al). Current-voltage (I vs V) measurements indicate that the device displays a classical behavior of a rectifying diode. The threshold value is approximately 5 V, and the onset for visible light emission occurs at ca. 10 V. From the a.c. electrical responses we infer that the active layer has a typical behavior of PLEDs where the real component of ac conductivity obeys a power-law with the frequency. Cole-Cole plots (Im(Z) vs. Re(Z)) for the device exhibit a series of semicircles, the diameter of which decreases with increasing forward bias. This PLED structure is modeled by a parallel resistance and capacitance combination, representing the dominant mechanisms of charge transport and polarization in the organic layer, in series with a resistance representing the ITO contact. Overall, the results presented here demonstrate the feasibility of LEDs made with LB films of PDHF-PV.
Keywords: Derivatives; Langmuir Blodgett films; Light emitting diodes; Polymer films; Sandwich structures; Substrates; Blue emissions; Polyfluorene derivative; Polymer light emitting devices (PLED); Surface pressure; Inorganic polymers